Analisis Model Soal Asesmen Sumatif Akhir Semester (ASAS) Mata Pelajaran PAI - Nurul Rambe; Syamsiah Depalina Siregar; Nelmi Hayati (An-Nuha, 2024)
This research was conducted at SMAN 1 Silangkitang, South Labuhan Batu Regency. The research method employed in this study is a descriptive qualitative approach, aiming to develop a model for the ASAS questions of PAI-BP subjects. The data sources taken are primary and secondary data sources. The primary data source in this research is the ASAS problem of class XII PAI-BP subjects, while the secondary data source is related to the data to be taken, such as through book sources, journals, and documents that support research data. The data collection techniques used in this study were observation, interviews and documentation. The technique used aims to collect data related to ASAS questions in PAI-BP subjects, which researchers use to analyze ASAS questions in PAI-BP subjects. The research results obtained were that the ASAS question model used in the PAI-BP lesson at SMAN 1 Silangkitang was a question with cognitive levels of LOTS (lower order thinking skills), MOTS (middle order thinking skills), and HOTS (high order thinking skills). The problem model used comprises three levels, featuring a total of 15 multiple-choice questions and 5 essay questions. There are around 15 LOTS level questions, 3 MOTS questions and 2 HOTS questions. The PAI-BP ASAS question contains material from the Merdeka curriculum, which is taken from the Merdeka class XI and XII curriculum books, specifically from material related to marriage, inheritance, and the development of Islam in the world.